Evidence-based treatment of foot and ankle injuries in runners - Barr, K. P.; Harrast, M. A. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
Foot and ankle injuries are common in runners. Treatment is becoming more evidence-based for the most common of these conditions; however, further research is needed to determine the best treatments for injuries that are encountered less commonly.